af015537: "We all know that defending human rights puts us personally at risk but we have to take up that challenge" - Amnesty International
"Affiche uitgegeven in 1995 door Amnesty International voor mensenrechten in El Salvador. Afbeelding: foto van vakbondsman Nazario de Jesús Gracias die doodgehakt werd bij de FEASIES-kantoren, aan de muur boven zijn lichaam hangt een kopie van de Universele Verklaring van de Rechten van de Mens. Opschrift: Trade Unionist Nazario de Jesús Gracias was hacked to death at the FEASIES offices. On the wall above his body is a copy of the Universal Declaration of Human Rights. March 1992. Tekst: WE ALL KNOW THAT DEFENDING HUMAN RIGHTS PUTS US PERSONALLY AT RISK BUT WE HAVE TO TAKE UP THAT CHALLENGE. Dr. Rafael Barrios, human rights lawyer, Colombia. FULL TEXT AVAILABLE AT AMSAB-ISH"